An Analysis on Students’ Ability in Using Simple Past Tense at Universitas Pahlawan Tuanku Tambusai - Wida Rianti (Journal of Innovative and Creativity, 2022)
This research is purposed to know about students’ ability at the second grade in using simple past tense. This research used qualitative descriptive analysis. The instrument of this research is a test. This research has only one variable. The variable is students’ ability in using simple past tense. The researcher chose the second grade students at Universitas Pahlawan Tuanku Tambusai. The respondent of the research consist of 32 students. The result of the test was analyzed to know the students’ ability in using the simple past tense. The finding of this research that the students' ability in using simple past tense at the second grade students of Universitas Pahlawan Tuanku Tambusai is in the less category with an average value of 30.16. There are 2 students (6.25%) were good, 6 students (18.75%) were medium, 11 students (34.37%) in the poor category, 13 students (40.63%) in the low category. The researcher hope the teacher should give more attention to the material of simple past tense and the teacher should give the suitable strategy to improve the students’ ability in using simple past tense.